Malignant Pilomatricoma with Lung Metastases: A Case Report and Literature Review - Lee, Nae-Ho; Park, Jung Kyun; Roh, Si-Gyun; Shin, Jin Yong; Chung, Yoon Kyu; Jang, Kyu Yun (Archives of Plastic Surgery, 2024)
Malignant pilomatricoma, an extremely rare tumor arising from hair follicles, most commonly occurs on the head, neck, and back. This tumor exhibits several noteworthy characteristics. First, it frequently recurs if it is incompletely excised and can occasionally metastasize to the lungs, bones, and lymph nodes. Additionally, it possesses unique histological features that aid in differentiating it from its benign counterpart, including atypical cells, multiple mitoses with ghost cells, nuclear polymorphisms, and necrosis accompanied by serial desmoplasia. While no definitive criteria have been established for the surgical management of this malignant tumor, it is recommended to perform wide local excision with a safety margin of at least ≥5 mm. To the best of our knowledge, very few cases of malignant pilomatricoma with lung metastasis have been reported in Korea. Here we report the case of a patient diagnosed of malignant pilomatricoma with lung metastasis who underwent wide local excision for a lesion on the flank.
Keywords: malignant pilomatricoma; lung metastasis; case reports